2019
DOI: 10.1126/sciadv.aau7566
|View full text |Cite
|
Sign up to set email alerts
|

A methylation-phosphorylation switch determines Plk1 kinase activity and function in DNA damage repair

Abstract: Polo-like kinase 1 (Plk1) is a crucial regulator of cell cycle progression; but the mechanism of regulation of Plk1 activity is not well understood. We present evidence that Plk1 activity is controlled by a balanced methylation and phosphorylation switch. The methyltransferase G9a monomethylates Plk1 at Lys209, which antagonizes phosphorylation of T210 to inhibit Plk1 activity. We found that the methyl-deficient Plk1 mutant K209A affects DNA replication, whereas the methyl-mimetic Plk1 mutant K209M prolongs me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 42 publications
2
48
0
1
Order By: Relevance
“…One study showed that SETD6 methylates PLK1 at K209 and K413 which keep mitosis in check and deficiency of SETD6 activity promotes cellular proliferation ( Feldman et al, 2019 ). The second study described that PLK1 activity is controlled by methyltransferase G9a at Lys209 ( Li et al, 2019 ), which antagonizes phosphorylation of T210 to inhibit PLK1 activity, and all these three sites are labelled in Supplementary Figure S3B . Since the methyl-deficient mutant K209A affects DNA replication, it is likely that Lys209 methylation is a switch for PLK1 function in DNA damage repair.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that SETD6 methylates PLK1 at K209 and K413 which keep mitosis in check and deficiency of SETD6 activity promotes cellular proliferation ( Feldman et al, 2019 ). The second study described that PLK1 activity is controlled by methyltransferase G9a at Lys209 ( Li et al, 2019 ), which antagonizes phosphorylation of T210 to inhibit PLK1 activity, and all these three sites are labelled in Supplementary Figure S3B . Since the methyl-deficient mutant K209A affects DNA replication, it is likely that Lys209 methylation is a switch for PLK1 function in DNA damage repair.…”
Section: Discussionmentioning
confidence: 99%
“…Current models suggest that ATR/CHK1 postpones the activation of CDK1 through Cdc25/Wee1 regulation, similar to the response to DNA damage (Goto et al, 2019;Sørensen and Syljuåsen, 2012). How PLK1 is suppressed during unperturbed proliferation is not clear, but after DNA damage, PLK1 activity is limited by dephosphorylation, disruption of Aurora A-Bora interaction, and direct methylation (Bruinsma et al, 2017;Hu et al, 2018;Li et al, 2019). In addition, PLK1 and CDK1 activity are tightly interlinked, and suppression of one can affect the other (Gheghiani et al, 2017;Lindqvist et al, 2009;Macůrek et al, 2008;Seki et al, 2008;Thomas et al, 2016;Vigneron et al, 2018).…”
Section: G1/s Brakementioning
confidence: 99%
“…As p38 is the primary effector of MKK3 signaling in response to cellular stress and cytokine stimulation(29), as well as chromatin conformational changes such as those observed in Figure 2, we hypothesized that DNA methylation also regulates p38 expression in CNFs and PNFs. Because methylation events can also impact kinase activation(30), we also assessed whether MAP2K3 methylation events affected downstream P38 activation. We identified a significant DMR (p = 1.66E-16) approximately 3.5 kb upstream of the MAPK14 gene, which encodes the p38α isoform.…”
Section: Resultsmentioning
confidence: 99%